Toxin-antitoxin systems and its biotechnological applications - Barbosa, Luiz Carlos Bertucci; Cangussu, Alex Sânder Rodrigues; Garrido, Saulo Santesso [UNESP]; Marchetto, Reinaldo [UNESP] (Academic Journals, 2014)
Toxin-antitoxin (TA) systems are important genetic modules composed by two elements: a toxin, that is always a protein, and an antitoxin, that can be a RNA or a protein and neutralizes the toxic effect of toxin. These systems are widespread in bacteria and archaea, found on plasmids and chromosomes. According to the nature of the antitoxin and its mode of interaction with the toxin, TA systems are grouped into five types. In general, the antitoxin is less stable than the toxin and is rapidly degraded in special conditions, leaving the toxin free to act on its cellular targets. TA modules are important in several events in cell physiology such as plasmid maintenance, formation of persister cells, stress resistance, protection from bacteriophages and regulation of biofilm formation, acting on crucial cellular processes including translation, replication, cytoskeleton formation and membrane integrity. TA systems components have proven to be very useful in biotechnology, being used to enhance cloning selection and protein expression in living bacterial cells. Furthermore, they are also considered as promising targets for the development of antibacterial drugs and can be used in gene therapy. Here, we reported current aspects and the application of TA modules in biotechnology research.
Keywords: Bacterial toxin-antitoxin (TA) systems; toxin; antitoxin; post-segregational killing (PSK)